A descriptive analysis of ICT usage at faculty offering Quantitative Science And Information Technology courses in northern region public higher learning institution / Wan Siti Esah Che Hussain...[et al.] - Che Hussain, Wan Siti Esah; Mansor, Kamarul Ariffin; Muhamat Daw Am, Siti Rafidah (2006)
This study is about the utilization of JCT in preparing the teaching materials and integrating them in delivering lecture. It focuses on finding out the JCT resources available for academic staff and to what extend do the lecturers used the JCT facilities available at their institutions . It will also look into the programs or workshops regarding JCT that are in demand among lecturers to upgrade their knowledge in JCT Lastly the study would like to find out what are the factors that hindered lecturers from using JCT in their field. The software used to analyze the data is SPSS v. J 2. 0. J. From the finding, we discovered that the utilization of JCT among the faculty members were at the average level that still need rooms for improvement. The result also showed that the level of JCT resources is inadequate with a mean score of 3. 79. Consequently, this factor becomes a major reason for educators not extensively utilizing JCT in teaching. Even though there is no significant barrier on JCT utilization found from the survey, many still under utilized the JCT facilities provided in their institution for unknown reasons. The recommendations/or this study are also included for further research and use.